THE CONTRIBUTION OF TRANSLATION IN THE BEGINNING OF ISLAMIC DEVELOPMENTS OF SCIENCE - Kurniawan, Iwan (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
It is believed that to master new knowledge from different cultures and countries, the role of translation is very pivotal. Because people speak and write different languages, the presence of translation as a tool to bridge the two sides is a must. Likewise, in the era of early Islam, such as the Umayyad and Abbasid caliphates, some Islamic and non-Islam scholars translated many scientific works into Arabic from other regions such as Greece, Persia, India, etc. These translated works later were learned and comprehended by Muslim scholars. They also developed those works meticulously to be better ones. There are some articles that discussed the translation practice in early Islamic caliphates but fewer papers that introduced disciplines and works that became the emphases of translation. This paper tries to explore what disciplines and what works became the focuses of translation activities from foreign languages into Arabic, which were carried out by Muslim and non-Muslim intellectuals at the beginning of Islam in the Umayyad and Abbasid caliphates. Using a Systematic literature Review which focuses on seven peer-reviewed articles, it is found there were several disciplines that became emphases of translation activities, such as Literature, arts, chemistry, city design, civil engineering, astronomy, medicine, philosophy, mathematics, etc.